L’orientation scolaire comme problème public (1964-1968) : sens et finalités d’une politique éducative - Paul Lehner (Recherches en Éducation)
The localized or structural study of school guidance overshadows the question of policy actors in terms of guidance and their representations. This article proposes to fill this blind spot by revealing through original sources the process of elaboration of the public problem of educational guidance. The cross analysis of the national archives reveal the actors involved in this reform, the space of the thinkable in which it is inscribed and, consequently, its aims.